Zelda and Ivy : keeping secrets - Kvasnosky, Laura McGee (Candlewick Press, 2009)
It's springtime, and little sister Ivy wants to prove she can keep a secret, but there are some secrets that are too good to keep. Big sister Zelda longs to play the perfect April Fool's Day prank, but can she outsmart the clever Ivy? And will opera star hopeful Zelda be upstaged by a butterfly in the final act? Fresh and funny, full of sugar and sass, this trio of tales about everyday life with siblings and friends is sure to strike a chord with young readers everywhere.